Toxicoproteomic analysis of pulmonary carbon nanotube exposure using LC-MS/MS. (2nd March 2015) - Hilton, Gina M.; Taylor, Alexia J.; McClure, Christina D.; Parsons, Gregory N.; Bonner, James C.; Bereman, Michael S.
Abstract: Toxicoproteomics is a developing field that utilizes global proteomic methodologies to investigate the physiological response as a result of adverse toxicant exposure. The aim of this study was to compare the protein secretion profile in lung bronchoalveolar lavage fluid (BALF) from mice exposed to non-functionalized multi-walled carbon nanotubes (U-MWCNTs) or MWCNTs functionalized by nanoscale Al2 O3 coatings (A-MWCNT) formed using atomic layer deposition (ALD). Proteins were identified using liquid chromatography tandem mass spectrometry (LC-MS/MS), and quantified using a combination of two label-free proteomic methods: spectral counting and MS1 peak area analysis. On average 465 protein groups were identified per sample and proteins were first screened using spectral counting and the Fisher's exact test to determine differentially regulated species. Significant proteins by Fisher's exact test ( p  < 0.05) were then verified by integrating the intensity under the extracted ion chromatogram from a single unique peptide for each protein across all runs. A two sample t -test based on integrated peak intensities discovered differences in 27 proteins for control versus U-MWCNT, 13 proteins for control versus A-MWCNT, and 2 proteins for U-MWCNT versus A-MWCNT. Finally, an in-vitro binding experiment was performed yielding 4 common proteins statistically different ( p  < 0.05) for both the in-vitro and in-vivo study. Several of the proteins found to be significantly different between exposed and control groups are known to play a key role in inflammatory and immune response. A comparison between the in-vitro and in-vivo CNT exposure emphasized a true biological response to CNT exposure.